APLIKASI SADD ADZ-DZARI’AH DALAM PERKEMBANGAN EKONOMI ISLAM - Andi Nurul Islamiah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
Prowth Islamic economy at the present time, there needs to be special attention related to the construction process, in which each stage of the process should pay attention to the good and bad, bring benefit or harm in the development of Islamic economics in accordance with the rules ofSharia. In line with the application of sadd adz-dzari'ah in the development of Islamic economics at the time, present it is necessary to pay attention to the law syara' and the rules of fiqh. This study aims to determine how good and bad sadd adz-dzari'ah . are when applied in the development of Islamic economics today. The method used is to use literature study (library research) with an approach descriptive then analyzed using the method Milles and Huberman with the stages of data reduction, data presentation and conclusions or verification . The results showed that the application of sadd adz-dzariah in the current development of Islamic economy is very vulnerable to lead to actions that cause damage/loss (mafsadah). Keywords: Sadd Adz-dzari'ah, Sadd Adz-dzari'ah Application, Islamic Economics